2016
DOI: 10.1038/srep29474
|View full text |Cite
|
Sign up to set email alerts
|

Spherulization as a process for the exudation of chemical cues by the encrusting sponge C. crambe

Abstract: Ecological interactions in the marine environment are now recognized to be partly held by chemical cues produced by marine organisms. In particular, sponges are sessile animals thought to rely on the bioactive substances they synthesize to ensure their development and defense. However, the mechanisms leading the sponges to use their specialized metabolites as chemical cues remain unknown. Here we report the constant release of bioactive polycyclic guanidinic alkaloids by the Mediterranean sponge Crambe crambe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 55 publications
1
29
0
Order By: Relevance
“…Indeed, the toxic compounds produced by this sponge could strongly select the fungal community able to grow on the sponge and/or inhibit the fungal growth in the isolation plates. From an ecological point of view, these compounds, once released, have teratogen effects on ascidian embryos, supporting the hypothesis that encrusting sponges like C. crambe, use toxic metabolites to mediate the colonization of new habitats (Ternon et al 2016).…”
Section: Mycobiota Vs Metabolomesupporting
confidence: 55%
See 2 more Smart Citations
“…Indeed, the toxic compounds produced by this sponge could strongly select the fungal community able to grow on the sponge and/or inhibit the fungal growth in the isolation plates. From an ecological point of view, these compounds, once released, have teratogen effects on ascidian embryos, supporting the hypothesis that encrusting sponges like C. crambe, use toxic metabolites to mediate the colonization of new habitats (Ternon et al 2016).…”
Section: Mycobiota Vs Metabolomesupporting
confidence: 55%
“…Actually, this sponge is well known for the production of toxic compounds (including polycyclic guanidine alkaloids), which are concentrated in the outer layer (Uriz et al 1996;Ternon et al 2016), making this organism scarcely colonisable by bacteria (Becerro et al 1997). In fact, C. crambe belongs to the -lowmicrobial-abundance sponges‖ characterized by an average amount of bacteria per g of sponge-wet weight lower than that of seawater (Sipkema et al 2015).…”
Section: Mycobiota Vs Metabolomementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, crambescidin 816 ( 80 ) displayed potent Ca 2+ antagonist activity and inhibited the acetylcholine-induced contraction of guinea pig ileum within very low concentrations [ 17 ], however, recent novel evidence showed that compound 80 partially blocked CaV and NaV channels in neurons, proposes that this compound might be included in decreasing the neurotransmitter release and synaptic transmission within the central nervous system [ 76 ]. Further, recent study proved that crambescidin 816 ( 80 ) could be stored into specialized sponge cells where it can be dispersed into the water affording a chemical umbrella surrounding the Crambe crambe sponge [ 77 ]. Recently, Botana and co-workers [ 78 ] reported important insights about the mechanism of the neurons cytotoxic activity of crambescidin 816 ( 80 ) in primary cultures of cortical neurons.…”
Section: Chemistry and Biology Of Natural Products Isolated From mentioning
confidence: 99%
“…Exometabolomics provides an opportunity to directly characterize the molecular interaction between microbes and their environment by profiling the types of molecules cellular organisms secrete (5). In terrestrial and limnic systems, these studies have advanced our understanding of microbial communities in soil organic matter cycling (6, 7), overflow metabolism of cultivable microorganisms (8, 9) and chemical ecology of the environment (10, 11). While intracellular metabolomic analyses of tissues from marine microbial cells to invertebrates is becoming increasingly more common (12-14), the defining characteristic of marine habitats - high salt concentration - limits exometabolomic analyses of the oceans to studies that require salt removal prior to metabolite extraction (10, 15, 16).…”
Section: Introductionmentioning
confidence: 99%